Emotional Intelligence Roles for Successful Academic Self-Management of Distance Learning - Risnawati, Erna; Pramitasari, Muktia; Mustapa, Noviana; Hanafi (Jurnal Pendidikan Terbuka Dan Jarak Jauh, 2024)
The advancement of distance learning in education is significant. Professionals and workers can study remotely without having to take time off from work to attend classes. Low academic self-management, on the other hand, is a common barrier faced by students enrolled in distance education programs. Therefore, Research on academic self-management and its determinants have been carried out. Respondents in this study were 180 (19-45 years old) early childhood department program students who were also teachers and lived in urban, suburban, and rural settings conducted by accidental sampling by online questionnaire. Mezzo's self-management scale and Schutte's brief emotional scale (BEIS) were used to measure academic self-management and emotional intelligence, respectively. Regression analysis was used to process the data. There are respondents from rural, suburban, and urban locations. The study's findings indicate that emotional intelligence has a 32.1% impact on academic self-management, with utilization dimension (38%) and emotional control dimensions (39,6%) having the largest effects. The findings of this study are expected to lead to new recommendations for managing emotional intelligence in the Open University student orientation program.